Piperlongumine Alleviates Mouse Colitis and Colitis-Associated Colorectal Cancer - Huang, Jia-Rong; Wang, Sheng-Te; Wei, Meng-Ning; Liu, Kun; Fu, Jing-Wen; Xing, Zi-Hao; Shi, Zhi (Frontiers in Pharmacology, 2020)
Colorectal cancer is one of the most common and lethal cancers in the world. An important causative factor of colorectal cancer is ulcerative colitis. In this study, we investigated the therapeutic effects of piperlongumine (PL) on the dextran sulfate sodium (DSS)-induced acute colitis and azoxymethane (AOM)/DSS-induced colorectal cancer mouse models. Our results showed that PL could inhibit the inflammation of DSS-induced mouse colitis and reduce the number of large neoplasms (diameter >2 mm) of AOM/DSS-induced mouse colorectal cancer by downregulation of proinflammatory cytokines cyclooxygenase-2 and interleukin-6 and epithelial-mesenchymal transition-related factors, β-catenin, and snail expressions, but fail to improve the colitis symptoms and to decrease the incidence of colonic neoplasms and the number of small neoplasms (diameter <2 mm). These data suggested that PL might be an effective agent in treating colitis and colorectal cancer.